Supramolecular assemblies of cis-palladium complexes dominated by C-H center dot center dot center dot Cl interactions - Moro, A. C.; Watanabe, F. W.; Ananias, S. R.; Mauro, A. E.; Netto, A. V. G.; Lima, A. P. R.; Ferreira, J. G.; Santos, R. H. A. (Elsevier B.V., 2006)
Two cis-related palladium(II) complexes [PdCl(2)(PPh(3))(tu)] (1) and [PdCl(2)(tmen)] (2) {PPh(3) = triphenylphosphine, tu = thiourea, tmen = N,N,N,N-tetramethylethylenediamine} have been synthesized and characterized by elemental analysis, IR and NMR spectroscopies, and single crystal X-ray diffraction. In 1, N-H center dot center dot center dot Cl hydrogen bonds are responsible for the formation of a dimer which connects to an adjacent one through weak C-H center dot center dot center dot Cl interactions, yielding 1D tapes. The crystal packing of compound 2 consists of zigzag ribbons of [PdCl(2)(tmen)] self-assembled by C-H center dot center dot center dot Cl hydrogen bonds which also holds the chains together, giving rise to a 2D layered structure. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: supramolecular chemistry; C-H center dot center dot center dot Cl hydrogen bonds; palladium(II); self-assembly